Comparative typing analyses of clinical and environmental strains of theCryptococcus neoformans/Cryptococcus gattiispecies complex from Ivory Coast. Issue 1 (January 2018) - Kassi, Fulgence K.; Bellet, Virginie; Drakulovski, Pascal; Krasteva, Donika; Roger, Frédéric; Valérie, Bedia‐Tanoh A.; Aboubakar, Touré; Doumbia, Adama; Kouakou, Gisèle A.; Delaporte, Eric; Reynes, Jacques; Yavo, William; et al.
Abstract : Purpose. : The aim of this study was to assess the biotope of the Cryptococcus neoformans/Cryptococcus gattii species complex from Ivory Coast, and clarify the possible epidemiological relationship between environmental and clinical strains. Methodology. : Samples from Eucalyptus camaldulensis ( n =136), Mangifera indica ( n =13) and pigeon droppings ( n =518) were collected from different sites close to the living environment of Ivorian HIV patients with cryptococcosis ( n =10, 50 clinical strains). Clinical and environmental strains were characterized by molecular serotyping and genotyping [RFLP analysis of the URA5 gene, (GACA)4, (GTG)5 and M13 PCR fingerprinting] and compared. Results/Key findings. : Environmental strains were recovered only from the pigeon droppings. In vitro susceptibility profiles showed that all strains were susceptible to fluconazole, flucytosine and amphotericin B. All environmental strains consisted of C. neoformans (A, AFLP1/VNI), whereas clinical strains included C. neoformans (A, AFLP1/VNI), C. neoformans x Cryptococcus deneoformans hybrids (AD, AFLP3/VNIII) and Cryptococcus deuterogattii (B, AFLP6/VGII). Two patients were co‐infected with both C. neoformans and C. neoformans x C. deneoformans hybrids. We noticed a low genetic diversity among the environmental samples compared to the high diversity of the clinical samples. Some clinical strains were genetically more similar to environmental strains than to other clinical strains, including those from the same patient. Conclusion. : These results provide new information on the ecology and epidemiology of the C. neoformans/C. gattii species complex in Ivory Coast.